Fabrication of PDEAEMA-Coated Mesoporous Silica Nanoparticles and pH-Responsive Controlled Release - Sun, Jiao-Tong; Hong, Chun-Yan; Pan, Cai-Yuan (Journal of physical chemistry. C, 2010)
Mesoporous silica nanoparticles (MSNs) are considered for potential scaffoldings in drug delivery due to their good biocompatibility and large pore volume, and it is the focus to find a suitable gatekeeper for the mesopores. In this paper, a reliable and versatile method of surface-initiated atom transfer radical polymerization (SI-ATRP) has been employed to prepare the hybrid poly(2-(diethylamino)ethyl methacrylate)-coated MSNs (MSN-PDEAEMA). The resultant hybrid nanoparticles with pH-sensitive polymer shell and MSN core were characterized by a series of techniques including high-resolution transmission electron microscopy, Fourier transform infrared spectroscopy, powder X-ray diffraction, and nitrogen adsorption isotherms. The pH-responsive PDEAEMA brushes anchored on MSNs could serve as a switch to control the opening and closing of the pores. Release of guest molecules was conducted at different pHs, and the results showed rapid release in acidic aqueous solution but very little leakage in alkaline solution. By adjusting the pH of the solution repeatedly, the release of encapsulated molecules could be switched on and off at will. We envision that this nanosystem should have potential applications in sited release of anticancer drug and gene delivery.